Studies on the synthesis, characterization, human serum albumin binding and biological activity of single chain surfactant–cobalt(III) complexes. (6th August 2015) - Vignesh, G.; Sugumar, K.; Arunachalam, S.; Vignesh, S.; Arthur James, R.; Arun, R.; Premkumar, K.
Abstract: The interaction of surfactant–cobalt(III) complexes [Co(bpy)(dien)TA](ClO4 )3 · 3H2 O (1) and [Co(dien)(phen)TA](ClO4 )3 · 4H2 O (2), where bpy = 2, 2′‐bipyridine, dien = diethylenetriamine, phen = 1, 10‐phenanthroline and TA = tetradecylamine with human serum albumin (HSA) under physiological conditions was analyzed using steady state, synchronous, 3D fluorescence, UV/visabsorption and circular dichroism spectroscopic techniques. The results show that these complexes cause the fluorescence quenching of HSA through a static mechanism. The binding constant ( K b ) and number of binding‐sites ( n ) were obtained at different temperatures. The corresponding thermodynamic parameters (∆ G °, ∆ H ° and ∆ S °) and Ea were also obtained. According to Förster's non‐radiation energy transfer theory, the binding distance ( r ) between the complexes and HSA were calculated. The results of synchronous and 3D fluorescence spectroscopy indicate that the binding process has changed considerably the polarity around the fluorophores, along with changes in the conformation of the protein. The antimicrobial and anticancer activities of the complexes were tested and the results show that the complexes have good activities against pathogenic microorganisms and cancer cells. Copyright © 2015 John Wiley & Sons, Ltd.